Testing for Market Power in the Norwegian Primary Aluminium Industry - Kjersti-Gro Lindquist (Statistics Norway, Research Department, 1994)
The hypothesis of market power in the Norwegian primary aluminium industry is tested using plant-level panel data. Economies of scale are found to be present, and Norwegian aluminium plants charge a procyclical price-cost margin that significantly exceeds zero. Consequently, the simple competitive hypothesis is rejected. The hypothesis that products are differentiated is not rejected, since several plants are found to charge a price permanently over the world market price. A decline in industry concentration internationally, which is assumed to increase the degree of competition, has no significant effect on the price-cost margins of Norwegian plants.
Keywords: C23; D21; D43; L61; 330; Market power; Differentiated products; Aluminium industry